The Effects of Planned Behavior, Professional Commitment, and Anticipatory Socialization on Whistleblowing Intention (Empirical Study of Accounting Students at Universitas Brawijaya) - MAULANA, REMA (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2019)
The purpose of this research is to analyze the effects of planned behavior,professional commitment, and anticipatory socialization on whistleblowing intention. Thepopulation in this study is accounting students of Universitas Brawijaya. This researchused primary data that are collected by offline questionnaire distribution. To examine therelation of theory of planned behavior, professional commitment and anticipatorysocialization with the whistleblowing intention used regression multiple test with SPSSsoftware version 23.0.0.0. The results of this study showed that all hypotheses areaccepted. The results of the analysis show percieved on planned behavior, professionalcommitment, and anticipatory socialization partially and simultaneously affect positivelytowards the intention of accounting students to whistleblow. From all the independentvariables, professional commitment has the most substantial influence towardswhistleblowing intention. This shows that students have perceptions about theenvironment of students who support it, and a positive attitude towards fraudulentcomplaints policy and have a view of what is a problem related on how to reveal thefraud.Keywords: planned behavior, professional commitment, anticipatory socialization,whistleblowing, and intention.